2019
DOI: 10.1002/jcp.28510
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of neural stem cells from adult astrocytes by using a single reprogramming factor

Abstract: Generating neural stem cells (NSCs) from astroglia as an abundant cell type in the mammalian brain has a promising outlook to be used in cell‐replacement therapy for treatment of neurodegenerative disorders and neuronal trauma. However, little is known about a single reprogramming factor that may lead to the generation of induced NSCs (iNSCs) from adult brain‐derived astrocytes in the absence of extrinsic inductive signals. Here, we show that zinc‐finger nuclear protein Zfp521 alone is sufficient for convertin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A key question to assess the outcome of direct conversion strategies is to which extent directly converted iNSCs recapitulate these characteristics [11,71]. In order to demonstrate selfrenewal potential and clonal growth ability, iNSCs were either cultivated as primary and secondary neurospheres [33,34], analyzed in colony formation assays [28,33,36,39,42,48,72], and/or passaged several times [11,13,14,26,30,32,33,38,57,59,60,73]. On the other hand, all iNSC populations have been reported to express pan-neural markers, to be at least bipotential, and to show self-renewal and clonal growth ( Table 2).…”
Section: Molecular and Cellular Characterization Of Inscsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key question to assess the outcome of direct conversion strategies is to which extent directly converted iNSCs recapitulate these characteristics [11,71]. In order to demonstrate selfrenewal potential and clonal growth ability, iNSCs were either cultivated as primary and secondary neurospheres [33,34], analyzed in colony formation assays [28,33,36,39,42,48,72], and/or passaged several times [11,13,14,26,30,32,33,38,57,59,60,73]. On the other hand, all iNSC populations have been reported to express pan-neural markers, to be at least bipotential, and to show self-renewal and clonal growth ( Table 2).…”
Section: Molecular and Cellular Characterization Of Inscsmentioning
confidence: 99%
“…Several groups succeeded in direct OSKM-and BSKM-independent conversion of somatic cells into iNSCs [12,28,[36][37][38]. Two studies reported the generation of iNSCs from human fibroblasts through inducible lentiviral transduction of Zfp521, a neurogenic TF, of cells cultured under hypoxic conditions in a reprogramming medium that contained valproic acid, CHIR99021, and SB431542 [36,39]. Another approach allowed to directly converting mouse and human fibroblasts, including cells derived from AD patients, into iNSCs with an efficiency higher than 0.5% [38].…”
Section: Transcription Factors Employed In Insc Generationmentioning
confidence: 99%
“…In addition, Zfp521 is a key factor in inducing differentiation of mouse embryonic stem cells into neural progenitors and its knockdown leads to inhibition of neural differentiation [42]. Zfp521 has been shown to be sufficient for the direct conversion of cultured human and mouse fibroblasts [31] as well as mouse astrocytes [32] into NSCs. Moreover, in comparison with Sox2 overexpression, Zfp521 demonstrated a higher efficiency in the conversion of astrocytes into iNSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that a single zinc-finger transcription factor, Zfp521, is sufficient for direct conversion of human and mouse fetal-and neonatal-derived fibroblasts into proliferating and multipotent iNSCs [31]. Our recent study indicated that mouse brain astrocytes could be reprogrammed in vitro to iNSCs by Zfp521 [32]. Since reprogramming efficiencies of ectopic transcription factors may differ in vivo, it is unclear whether Zfp521 can convert the fate of astrocytes in the adult rat spinal cord and improve function following SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors are proteins that either up-regulate or down-regulate the transcription of specific genes, generally by interacting with the RNA polymerase's transcription complex or by down-regulating others factors involved in stimulating transcription [194][195][196][197][198]. Currently, the reprograming of astrocytes into neurons may be performed with simpler procedures that overexpress a single transcription factor [193,199]. MicroRNAs are noncoding sequences of RNA (often of about 22 nucleotides) that may regulate gene expression at the posttranscriptional level, generally by selectively binding to a particular mRNA which produces the silencing of a specific RNA [200,201].…”
Section: The Global Activation Of the Neuroprotective Functions Of Astrocytesmentioning
confidence: 99%